Label‐free bead‐based metallothionein electrochemical immunosensor. Issue 16 (20th July 2015) - Nejdl, Lukas; Nguyen, Hoai Viet; Richtera, Lukas; Krizkova, Sona; Guran, Roman; Masarik, Michal; Hynek, David; Heger, Zbynek; Lundberg, Karin; Erikson, Kristofer; Adam, Vojtech; Kizek, Rene
Abstract : A novel microfluidic label‐free bead‐based metallothionein immunosensors was designed. To the surface of superparamagnetic agarose beads coated with protein A, polyclonal chicken IgY specifically recognizing metallothionein (MT) were immobilized via rabbit IgG. The Brdicka reaction was used for metallothionein detection in a microfluidic printed 3D chip. The assembled chip consisted of a single copper wire coated with a thin layer of amalgam as working electrode. Optimization of MT detection using designed microfluidic chip was performed in stationary system as well as in the flow arrangement at various flow rates (0–1800 μL/min). In stationary arrangement it is possible to detect MT concentrations up to 30 ng/mL level, flow arrangement allows reliable detection of even lower concentration (12.5 ng/mL). The assembled miniature flow chip was subsequently tested for the detection of MT elevated levels (at approx. level 100 μg/mL) in samples of patients with cancer. The stability of constructed device for metallothionein detection in flow arrangement was found to be several days without any maintenance needed.